Analysis of Legal Protection Concepts for Workers in the Informal Sector Based on Indonesian Laws and Regulations: Analisis Konsep Perlindungan Hukum Terhadap Pekerja di Sektor Informal Berdasarkan Ketentuan Peraturan Perundang-Undangan di Indonesia - Grace Avianti; Gunardi Lie (Academia Open, 2025)
General Background: Informal sector workers play a crucial role in Indonesia’s labor market yet remain highly vulnerable due to limited legal protection. Specific Background: Existing regulations—including the Manpower Act, Job Creation Law, BPJS Law, and Government Regulation No. 35/2021—primarily regulate formal employment, leaving informal workers without explicit safeguards. Knowledge Gap: Despite their dominant share in the workforce, the normative framework insufficiently addresses the unique characteristics of informal employment and the widespread misclassification practices used to avoid employers’ legal obligations. Aims: This study analyzes the legal concept of protection for informal workers and evaluates how judicial reasoning in Supreme Court Decision No. 1049 K/Pdt.Sus-PHI/2023 reinforces such protection. Results: Findings indicate fragmented regulations that normatively recognize worker rights but fail to provide comprehensive operational mechanisms, requiring judicial interpretation to uphold substantive justice. Novelty: This study highlights how the Supreme Court’s substantive approach—affirming factual employment elements over formal documentation—fills normative gaps and corrects lower-court formalism. Implications: Strengthening explicit legal recognition of informal workers, enforcing BPJS obligations, and standardizing judicial tests for employment status are essential to ensure equitable and inclusive labor protection in Indonesia. Highlights: The legal framework for informal workers remains fragmented and insufficient. The Supreme Court prioritizes factual employment elements over formal documents. Strengthened regulation is needed to ensure equitable protection for informal labor. Keywords: Legal Protection, Informal Workers, Employment Relationship, Supreme Court, Labor Regulation